2020
DOI: 10.3390/genes11040388
|View full text |Cite
|
Sign up to set email alerts
|

Insights through Genetics of Halophilic Microorganisms and Their Viruses

Abstract: Halophilic microorganisms are found in all domains of life and thrive in hypersaline (high salt content) environments. These unusual microbes have been a subject of study for many years due to their interesting properties and physiology. Study of the genetics of halophilic microorganisms (from gene expression and regulation to genomics) has provided understanding into mechanisms of how life can occur at high salinity levels. Here we highlight recent studies that advance knowledge of biological function through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Halophilic microorganisms are widely distributed in high-salt environments such as oceans, salt lakes, salt fields, and pickled foods ( Banciu et al, 2019 ; Montalvo-Rodríguez and Maupin-Furlow, 2020 ). As a microbial resource with diverse application prospects, halophils have attracted extensive attention at home and abroad because of their special physiological characteristics, metabolic capabilities, interactive community composition, and genetic resources ( Dumorné et al, 2017 ; Hasanzadeh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Halophilic microorganisms are widely distributed in high-salt environments such as oceans, salt lakes, salt fields, and pickled foods ( Banciu et al, 2019 ; Montalvo-Rodríguez and Maupin-Furlow, 2020 ). As a microbial resource with diverse application prospects, halophils have attracted extensive attention at home and abroad because of their special physiological characteristics, metabolic capabilities, interactive community composition, and genetic resources ( Dumorné et al, 2017 ; Hasanzadeh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to non-extremophilic settings, not much is known about these halophilic systems. Additional research on these viruses may eventually lead to genetic systems and a better understanding of these high-salinity microbial environments [ 65 ].…”
Section: Halophilic/alkalophilic Virusesmentioning
confidence: 99%
“…Genomic and molecular studies have revealed the differential expression of many genes involved in the biosynthesis of secondary metabolites in these organisms compared to their expression under normal conditions [ 151 , 152 ]. The obtained compounds from these fungi can potentially be used in industrial and biotechnological fields, as well as in the production of β-carotene, ectoine, and bio-rhodopsin for optical computing, and in holograms, biosensors, photoelectric devices, cosmetics, preservatives, fermented food products, the manufacturing of bioplastics and artificial retinas, bio-surfactants and exopolysaccharides, biofuels, pigments for colouring, and even bioremediation [ 153 , 154 , 155 , 156 , 157 ].…”
Section: Halophiles and Other Poly Extremophilesmentioning
confidence: 99%